Inclusion of homologous DNA in nuclease‐mediated gene targeting facilitates a higher incidence of bi‐allelically modified cells. (18th September 2015) - Beaton, Benjamin P.; Kwon, Deug‐Nam; Choi, Yun‐Jung; Kim, Jae‐Hwan; Samuel, Melissa S.; Benne, Joshua A.; Wells, Kevin D.; Lee, Kiho; Kim, Jin‐Hoi; Prather, Randall S.
Abstract Background Recent advancements in gene editing techniques have increased in number and utility. These techniques are an attractive alternative to conventional gene targeting methods via homologous recombination due to the ease of use and the high efficiency of gene editing. We have previously produced cytidine monophosphate‐N‐acetylneuraminic acid hydroxylase (CMAH) knockout (KO) pigs in a Minnesota miniature pig genetic background. These pigs were generated using zinc‐finger nucleases (ZFNs) in combination with donor DNA containing a total homology length of 1600 bp (800‐bp homology on each arm). Our next aim was to introduce the targeted disruption of alpha‐1, 3‐galactosyltransferase (GGTA1) in the CMAH KO genetic background and evaluate the effect of donor DNA homology length on meganuclease‐mediated gene targeting. Methods Zinc‐finger nucleases from a previous CMAH KO experiment were used as a proof of concept to identify a correlation between the length of donor DNA homology and targeting efficiency. Based on those results, experiments were designed to use transcription activator‐like effector nucleases (TALENs) to generate bi‐allelically modified GGTA1 cells using donor DNAs carrying various lengths of homology. Donor DNA was designed to symmetrically flank the predicted cleavage sites in CMAH and GGTA1 for both ZFN and TALEN cleavage sites, respectively. For both genes, the length of total homology ranged from 60 to 1799 bp. Sialyltransferase gene expression profiles were evaluated in CMAH and GGTA1 double KO pig cells and were compared to wild‐type and CMAH KO cells. Results Introduction of donor DNA with ZFNs demonstrated that small amounts of homology (60 bp) could facilitate homology‐directed repair during ZFN‐mediated targeting of CMAH; however, donor DNA with longer amounts of homology resulted in a higher frequency of homology‐directed repair. For the GGTA1 KO experiments that used TALENs and donor DNA, donor DNA alone did not result in detectable bi‐allelic conversion of GGTA1. As the length of donor DNA increased, the bi‐allelic disruption of GGTA1 increased from 0.5% (TALENs alone, no donor DNA present) to a maximum of 3% (TALENs and donor DNA with total homology of 1799 bp). Inclusion of homologous donor DNA in TALEN‐mediated gene targeting facilitated a higher incidence of bi‐allelically modified cells. Using the generated cells, we were able to demonstrate the lack of GGTA1 expression and the decrease in gene expression sialyltransferase‐related genes. Conclusions The approach of using donor DNA in conjunction with a meganuclease can be used to increase the efficiency of gene targeting. The gene editing methods can be applied to other genes as well as other mammalian systems. Additionally, gene expression analysis further confirms that the CMAH/GGTA1 double KO pigs can be a valuable source for the study of pig‐to‐human xenotransplantation.